Evaluation of the Family Hope Program (PKH) in Cilengkrang Village, Cilengkrang Subdistrict, Bandung Regency - pratama saputra, fauzi (GoResearch - Research & Publishing House, 2025)
This study aims to evaluate the Family Hope Program (PKH) policy in Cilengkrang Village, Cilengkrang Subdistrict, Bandung Regency. The evaluation is based on several dimensions, namely effectiveness, equity, and consistency, which are still not optimal. The method used in this study is a qualitative method with data collection techniques through interviews, observations, and documentation studies. The results of the study indicate that there are several factors hindering the implementation of PKH in Cilengkrang Village. These obstacles include inaccurate data validation, inappropriate targeting of program participants, and the accumulation of aid funds in participants' accounts that are not immediately used. To overcome these obstacles, several improvement efforts were made. These efforts include aligning program data with participants' personal data to ensure accuracy, re-verifying the eligibility of program participants, and withdrawing all assistance funds from participants' accounts without exception to ensure that the assistance is utilized effectively.